Urban water security: a comparative study of cities in the arid Americas. (April 2020) - Díaz-Caravantes, Rolando E; Zuniga-Teran, Adriana; Martín, Facundo; Bernabeu, Marta; Stoker, Philip; Scott, Christopher
In this study we analyse how three cities in the arid Americas have addressed urban growth while facing water scarcity: Hermosillo, Mexico; Mendoza, Argentina; and Tucson, USA. We use the urban water security framework to examine five domains of water management: sociodemographic, economic, technological, ecological and governance (SETEG). Our analysis indicates that, in spite of water scarcity, urban growth has been promoted in the three cities. We argue that this expansion, although encouraged for economic development, is not sustainable in the long term. In the three cities, groundwater plays a major role in water supply, but growth has negatively affected riparian ecosystems, the health of the aquifers and access to domestic water. In order to pursue water security, several options are essential to enhance social–ecological system resilience. These include limits or reduction of urban expansion, reuse of treated effluent for riparian conservation, and community conservation efforts such as rainwater harvesting and other green infrastructure practices.